Optimization of the Detection Method for Phosphorylated α-Synuclein in Parkinson Disease by Skin Biopsy - Liu, Xiaojing; Yang, Jing; Yuan, Yanpeng; He, Qian; Gao, Yuan; Jiang, Chenyang; Li, Lanjun; Xu, Yuming (Frontiers in Neurology, 2020)
Background: Recent studies have found deposition of phosphorylated α-synuclein (p-syn) in Parkinson disease (PD) patients’ skin, indicating p-syn may be a potential biomarker of PD. However, the sensitivity of the p-syn detection varied largely from 5.3% to 100%, this influenced the clinical use of this detection method to some extent. Objective: This study aimed to optimize the skin biopsy method for detecting p-syn deposition in patients with PD. Methods: Ninety PD patients and 30 healthy controls underwent skin biopsies at 2–3 of the following sites: the distal leg, thigh, cervical region, or forearm. Skin biopsy samples were cut to 50-μm and 15-μm thickness sections. Deposition of p-syn were detected by using double immunofluorescence labeling of protein gene production 9.5(PGP9.5) /p-syn. Statistical data analysis was performed using SPSS 25.0 software. Results: Deposition of p-syn were found in 75/90 PD patients but not in healthy controls (p < 0.001). The positive deposition rate of p-syn in the single cervical site was significantly higher than that in the distal leg, thigh, and forearm site. Two samples from the cervical region had a higher p-syn positive rate compared to single cervical site (90.5% vs 66.7%, p=0.037). There was no significant difference between the p-syn positive rate of samples from the distal leg/cervical sites and 2 samples from cervical region (80% vs 90.5%, p=0.261). Next, the p-syn positive deposition rate of 2-biopsy samples including distal leg/cervical sites and double samples in the cervical site were comparable to the 3-biopsy samples. The 50-μm section had a significantly higher p-syn positive rate than the 15-μm section(p=0.049). Conclusions: Two biopsy sites (cervical/distal leg) or 2 samples from the cervical site were considered to be priority biopsy sites for detecting p-syn in PD patients. Thick sections may provide a higher p-syn positive rate than thin sections for skin biopsies. These findings provide an optimized p-syn detection method, indicate the valuable pathology biomarker of PD and will promote the clinical use of skin biopsy in the future.